Conceptual Properties of Islamic Economic Modeling: Complexity, Nonlinearity, and Endogeneity in Epistemological Perspectives - Choudhury, Masudul Alam (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
This paper introduces a new perspective of economic reasoning and analysis pertaining to situations of complexity combined with nonlinearity and endogenous relations among interacting, integrating and evolutionary entities. The entities comprise multi-variables representing different embedded systems that encompass economy, society, science, and ethics. In the emergent model of endogenous inter-causal relationships between such entities the ontological perspective assumes the nature of evaluating inter-causal intra- and inters- systemic relations by means of formalism belonging to functional ontology of mathematical forms (Gruber, 1993), as opposed to invoking metaphysical ontological speculation. The functional ontological approach to structure and formalize leads to a new framework of economic reasoning in the presence of embedded systems that continuously participate and complement, as opposed to being subjected to the central postulate of marginal rate of substitution and exogenous treatment of knowledge in mainstream economics. The continuous phenomenon of interaction, integration, and evolutionary (IIE) learning in such inter-causal systems establish ethical endogeneity. Thus, philosophical background of economic reasoning is invoked in the functional epistemological formalism of the interactive, integrative, and evolutionary systems. That is sush systems are characterized by IIE-learning processes induced by the episteme of unity of knowledge.